Working Capital Behavior, Risk and Profitability: Empirical Study of Manufacturing Companies in Indonesia - Sulastri, Sulastri; Isnurhadi, Isnurhadi; Widiyanti, Marlina; Saftiana, Yulia (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
This research aims to empirically test the influence of industry volatility, sales growth,and company size on working capital behavior and its impact on liquidity risk, operational risk, financial risk, andprofitability. This research was conducted on industrial sector companies listed on the Indonesian Stock Exchange. Data consists ofpanel data from 2018-2022 totaling 272 samples after screening for outliers and normality. Structural equation modeling is employed to test the recursive model. This research proves that there is a positive influence of industry volatility on working capital aggressiveness.Company size influences working capital behaviornegatively, andsales growth has no influence on it. Furthermore, working capital behavior influences liquidiy risk positively and negatively on financial risk, but has no influence on operational risk.This research proves that simultaneously liquidity risk has a positive effect and financial risk has a negative effect on profitability.Operational risk has no effect on profitability.